Effects of Toasting Time on Digestive Hydrolysis of Soluble and Insoluble 00‑Rapeseed Meal Proteins - Salazar Villanea, Sergio (2017)
La Universidad de Costa Rica proporcionó una beca para el programa de doctorado de Sergio Salazar Villanea